Baseline renal functions predict the effect of canakinumab on regression of proteinuria in patients with familial Mediterranean fever - Tolga Yildirim (Elsevier, 2021)
Introduction and objectives: Canakinumab, an IL-1 blocking drug, decreases the frequency and severity of the attacks and decreases the proteinuria level in colchicine resistant/intolerant familial Mediterranean fever (FMF) patients. However, it is not known whether patients with impaired or preserved renal functions respond differently to IL-1 blocking therapies in terms of proteinuria reduction and progression of kidney dysfunction which was the aim of this study. Materials and methods: Adult FMF subjects with biopsy proven amyloidosis who had 24-h urine protein excretion > 150 mg/day before initiation of canakinumab were divided into two groups as patients with preserved renal function (GFR ≥ 60 mL/min) and patients with impaired renal function (GFR < 60 mL/min). The response in proteinuria and renal functions are compared between two groups in this cross-sectional study. Results: A total of 18 patients (11 with preserved and 7 with impaired renal function) were included in this study. Although proteinuria levels of both groups were similar at the baseline and at six months after initiation of canakinumab, proteinuria at 12 months was significantly lower for patients with preserved renal function compared to patients with impaired renal function (2462 ± 1760 mg/day vs. 7065 ± 3035 mg/day respectively, p = 0.02). All of the patients with preserved renal function had more than 50% decrease in proteinuria at 12 months compared to baseline values, while none of the patients with impaired renal function had more than 50% decrease in proteinuria. Conclusions: Canakinumab, an IL-1 blocking agent, is not effective in decreasing proteinuria in FMF patients with already impaired renal functions and should be started early in the course of disease to prevent renal impairment. Resumen: Introducción y objetivos: El canakinumab, un fármaco bloqueante de la IL-1, disminuye la frecuencia y la gravedad de los ataques y reduce el nivel de proteinuria en pacientes con fiebre mediterránea familiar (FMF) resistentes o intolerantes a la colchicina. Sin embargo, se desconoce si los pacientes con función renal deteriorada o preservada responden de forma diferente a los tratamientos de bloqueo de la IL-1 en cuanto a la reducción de la proteinuria y la progresión de la disfunción renal, que era el objetivo de este estudio. Materiales y métodos: Los sujetos adultos con FMF y amiloidosis demostrada por biopsia que tenían una excreción de proteínas en orina de 24 h > 150 mg/día antes de iniciar el tratamiento con canakinumab, se dividieron en dos grupos: pacientes con función renal preservada (TFG ≥ 60 mL/min) y pacientes con función renal deteriorada (TFG < 60 mL/min). En este estudio transversal se comparan la respuesta en la proteinuria y las funciones renales entre dos grupos. Resultados: En este estudio se incluyeron 18 pacientes (11 con función renal preservada y siete con función renal deteriorada). Aunque los niveles de proteinuria de ambos grupos fueron similares al inicio y a los seis meses de iniciar el tratamiento con canakinumab, la proteinuria a los 12 meses fue significativamente menor en los pacientes con función renal preservada, en comparación con los pacientes con función renal deteriorada (2.462 ± 1.760 mg/día vs. 7.065 ± 3.035 mg/día, respectivamente, p = 0,02). Todos los pacientes con función renal preservada presentaron una disminución de la proteinuria superior al 50% a los 12 meses, en comparación con los valores iniciales, mientras que ninguno de los pacientes con función renal deteriorada presentó una disminución de la proteinuria de más del 50%. Conclusiones: El canakinumab, un fármaco bloqueante de la IL-1, no es eficaz en la disminución de la proteinuria en pacientes con FMF que ya tienen la función renal deteriorada, y el tratamiento debe iniciarse en una fase temprana de la evolución de la enfermedad para prevenir una insuficiencia renal.